FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP RETURN ON ASSET BANK PEMBANGUNAN DAERAH DI INDONESIA TAHUN 2011 – 2014 - Sunarso, Amin Fahrudi, Setyaningsih Sri Utami & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
Profitability is the most appropriate indicators to measure the performance of a bank. One measure of profitability of banks using the ROA. ROA is a ratio that illustrates the ability of banks to make profits overall objective of this study was to analyze the influence of Capital Adequacy Ratio, liquidity ratio, credit risk, operational eficency and firm size (size) of the Return on Assets in Regional Development Bank in Indonesia. This research is an empirical study on the Regional Development Bank in Indonesia in 2011 - 2014. The data type using quantitative and qualitative data. The data source using primary data and secondary data. The study population Regional Development Bank listed in the Directory Indonesian Banking during 2011 through 2014 are 26 Regional Development Banks in Indonesia and the whole is used as a sample with a total sampling technique. Source data used are secondary data in the form of financial statements of the Bank for Regional Development 2011-2014. Data collection techniques used in this research is the study documentation. Study documentation in this study were obtained from www.bi.go.id..Teknik data analysis using classical assumption test, multiple linear regression, t-test, F and coefficient of determination. The results showed that the Capital Adequacy Ratio significant negative effect on the return on assets Regional Development Bank in Indonesia. Liquidity Ratio (LDR) significantly affects the return on assets Regional Development Bank in Indonesia. Credit Risk (Non Performing Loan) but no significant negative impact on the return on assets Regional Development Bank in Indonesia. Operational Eficency (ROA) positive and significant impact on the return on assets in the Regional Development Bank in Indonesia. Firm size (size) but not significant positive effect on return on assets in the Regional Development Bank in Indonesia.Keywords: CAR, LDR, NPL, BOPO,ROA